The Effect of Price on Consumer Purchase Decisions - Kurniawan Gea; Maria Magdalena Bate’e; Emanuel Zebua; Aferiaman Telaumbanua (Golden Ratio of Data in Summary, 2024)
This study aims to determine whether financial inclusion has a positive effect on the sustainability of the SME sector in Lotu District, North Nias Regency, and to determine how much influence financial inclusion has on the sustainability of the SME sector, and to determine whether financial inclusion can overcome the challenges experienced by SME actors. The study was conducted in Lotu District, North Nias Regency. The research method used is a quantitative method with data collection through the distribution of questionnaires, documentation, and interviews, observations. The respondents in this study were 63 SME respondents. The results of this study indicate that the influence of financial inclusion has an influence on the sustainability of the SME sector by 20.4%. With increasing financial inclusion, it will further encourage SME actors to develop their businesses in the future.